Unlearning school attendance and its problems: Moving from historical categories to postmodern dimensions - Kearney, Christopher A.; Gonzálvez, Carolina (Frontiers in Education, 2022)
School attendance and its problems have been a focus of myriad stakeholders for over a century, which has led both to important advancements in this area as well as compartmentalized categorical approaches to explain at least part of the vast ecology of these issues. Recent seismic events and changes, however, have provided a unique opportunity to unlearn calcified notions of school attendance and its problems and to consider more inclusive paradigms. This article focuses on several categorical approaches that have been historically a focus of research, health-based clinical work, and educational and social policy in this area: defining school attendance problems, demarcating school attendance problems, subtyping school attendance problems, risk and protective factors for school attendance/problems, interventions for school attendance problems, and school completion. For each area, alternative dimensional approaches are discussed that are emerging from different disciplines and that may provide additional flexibility and comprehensiveness for avenues of endeavor relevant to a postmodern era. The article concludes with a call to abandon historical, discipline-specific, categorical silos in favor of a spectrum of postmodern, multidisciplinary systemic-analytic collaborations and shared alliances to better conceptualize and manage the full ecology of school attendance and its problems.